2015
DOI: 10.1007/s13193-015-0423-y
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngocutaneous Fistula Incidence After PMMC Patch Pharnygoplasty for Post Laryngectomy Defect Reconstruction – Predictive Factors, Our Experience at KMIO

Abstract: To analyse pharyngocutaneous fistula, post Pectoralis major myocutaneous patch pharnygoplasty, and its association with various tumor, patient and treatment related factors. It is a retrospective study that included 48 patients who underwent laryngectomy and PMMC patch pharyngeal reconstruction from year 2009 to 2013. We studied the previously reported factors that could influence fistula formation such as age, gender, previous radiotherapy, previous tracheostomy, location of tumor, extent of tumor, tumor volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…A total of 1156 studies were further narrowed down to 19 [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] peer-reviewed publications, for a total of 132 patients ( Table 1) pharyngocutaneous fistulas (3.1%) were complicated by carotid blowout. (Table 2) Most salivary fistulas could be diagnosed clinically.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 1156 studies were further narrowed down to 19 [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] peer-reviewed publications, for a total of 132 patients ( Table 1) pharyngocutaneous fistulas (3.1%) were complicated by carotid blowout. (Table 2) Most salivary fistulas could be diagnosed clinically.…”
Section: Resultsmentioning
confidence: 99%
“…However, 2 separate retrospective studies found no statistically differences in terms of choice of treatment between their fistula patients with and without radiotherapy exposure 14,17 .…”
Section: Tissue Characteristicsmentioning
confidence: 98%